ANALISIS STRUKTUR EKONOMI DAN TRANSFORMASI TENAGA KERJA SEKTORAL DI KAWASAN ASIA SELATAN PERIODE 1990-2024 - Siti Mutmainah; Syaparuddin; Nurhayani (STKIP Subang, 2026)
This study aims to analyze the sectoral economic structure and labor transformation in South Asia during 1990-2024. Using descriptive and quantitative methods with Structural Change Index (SCI), Relative Productivity (RP), and Shift Share analysis, the results show that all countries experienced a decline in the primary sector and an increase in the tertiary sector in GDP. Bangladesh was the only country that significantly increased its secondary sector contribution. Nepal showed the most extreme shift but directly from agriculture to services without strong industrialization. Pakistan experienced premature deindustrialization, while Sri Lanka faced structural stagnation. RP proved that Bangladesh maintained above-average productivity in both secondary and tertiary sectors. Shift Share analysis confirmed Bangladesh had the best competitive advantage in both sectors, while India and Sri Lanka began to experience declining industrial competitiveness.